Using Smartphones to Help People with Intellectual and Sensory Disabilities Perform Daily Activities - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Zimbaro, Carmen; Chiariello, Valeria (Frontiers in Public Health, 2017)
Background People with mild-to-moderate intellectual disability and sensory impairments often fail to take initiative in starting and carrying out daily activities, with negative consequences for their occupational condition and social status. Their failure seems due to their inability to determine the right time for the activities and to remember all the activity steps. Aim This study assessed a smartphone intervention, which was designed to help eight participants (four presenting with intellectual disability and blindness and four presenting with intellectual disability and hearing impairment) to independently start and carry out daily activities at appropriate times. Method The intervention was introduced according to a non-concurrent multiple baseline design across participants. During the intervention, each participant was provided with a smartphone, which was fitted with the time schedule of his or her activities and the verbal or pictorial instructions for the single steps of those activities. When the time for an activity was reached, the participant was automatically reminded to start that activity and, thereafter, he or she was presented with the instructions for it. Results The use of the smartphone intervention promoted great improvement over the baseline for all participants. That is, the participants managed to (a) independently start the activities at the scheduled times and (b) carry out those activities with high levels of accuracy. Conclusion A smartphone intervention, such as that used in this study, may help people with mild-to-moderate intellectual disability and sensory impairments to successfully engage in daily activities.